Actualization Of Pancasila Values At The Al-Amin Islamic Boarding School, Sumenep - Edi Awan; Zainal Abidin (Indonesian Journal of Science, Technology and Humanities, 2024)
This research was conducted to determine the actualization of Pancasila values ​​at the Al-Amin Prenduan Islamic boarding school in Sumenep and to find out how Pancasila values ​​are implemented at the Prenduan Islamic boarding school in Sumenep. The population in this study was 4,000 people and a sample of 100 students was taken. Data collection techniques were carried out by means of observation, interviews and documentation. By coming and directly examining the activities of the students at the Al-Amin Prenduan Islamic boarding school, Sumenep for 19 days. By understanding the circumstances and processes of activities and socialization among fellow students. The results of the research show that there is actualization of Pancasila values ​​at the Al-Amin Prenduan Islamic boarding school, Sumenep. Strengthening the first principle is strengthened through congregational prayers five times a day followed by reciting the Koran together, reciting istighatsah every day before the morning call to prayer, reading tahlil and prayers every Friday night, as well as reciting recitations after every morning prayer and also religious material. Strengthening the second principle is strengthened through extracurricular activities. Strengthening the third principle is strengthened through community service activities every Friday. Strengthening the fourth principle is strengthened through deliberation activities in every activity, making decisions on selecting the chairman. Strengthening the fifth principle is strengthened through correct group division and the provision of prizes for students who excel and punishments for students who violate them.